2005
DOI: 10.1002/jsfa.2149
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microbial transglutaminase on autolysis and gelation of lizardfish surimi

Abstract: In the absence of microbial transglutaminase (MTGase), the textural properties of lizardfish surimi (Saurida spp) improved when pre-incubated at 4 and 25 • C for 24 and 4 h, respectively. MTGase optimally catalyzed incorporation of monodansylcadaverine (MDC) into surimi at 40 • C. Addition of MTGase appeared to reduce autolytic activity at 25 and 40 • C, but had no effect on autolytic activity at 65 • C. Breaking force and deformation of lizardfish surimi significantly improved when 0.1 unit MTGase g −1 surimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2008
2008
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…MTGase played the role in the cross-linking of golden threadfin bream and pollack actomyosin as indicated by gradual decrease in MHC band. Yongsawatdigul and Piyadhammaviboon (2005) reported that protein crosslinking in lizardfish surimi was catalyzed by MTGase at 40 1C for 1 h prior to heating at 90 1C for 30 min. It was noted that MHC and actin bands of surimi gel added with fish gelatin decreased as the gelatin level added increased.…”
Section: 4mentioning
confidence: 99%
“…MTGase played the role in the cross-linking of golden threadfin bream and pollack actomyosin as indicated by gradual decrease in MHC band. Yongsawatdigul and Piyadhammaviboon (2005) reported that protein crosslinking in lizardfish surimi was catalyzed by MTGase at 40 1C for 1 h prior to heating at 90 1C for 30 min. It was noted that MHC and actin bands of surimi gel added with fish gelatin decreased as the gelatin level added increased.…”
Section: 4mentioning
confidence: 99%
“…No decrease was found in the percentage share of actin. It is hypothesised that-similarly to the action of heat on proteins-transglutaminase causes changes by a partial development of polypeptide chains and as a consequence in an enhanced availability of hydrophobic fragments [29]. However, in other fragments of the chain protein molecules undergo aggregation, combined with a reduction in availability of hydrophobic fragments and a loss of solubility [30].…”
Section: Electrophoretic Analysis Of Myofibril Preparationmentioning
confidence: 99%
“…However, the proteolysis can be inhibited by beef plasma protein (BPP) and others (Kang & Lanier, 2005;Morrissey, Wu, Lin, & An, 1993;Park, Yongsawatdigul, & Lin, 1994). Transglutaminase (TGase) added and also present in fish muscle (i.e., endogenous TGase) results in higher texture quality (Folk, 1980;Park, 2005;Takeda & Seki, 1996;Yongsawatdigul & Piyadhammaviboon, 2005;Yongsawatdigul, Worratao, & Park, 2002). Potato starch (PS) is typically added to fish products because of gelatinization (Park, 2005).…”
Section: Introductionmentioning
confidence: 99%